Work Force Absorption on the Verge of Demographic Bonus Era at the Special Capital Region of Jakarta - Sabrina Mutmainah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
As Indonesia's largest economic hub, DKI Jakarta plays a crucial role in national growth, reflected in its high Gross Regional Domestic Product (GRDP) and workforce absorption in sectors such as trade, transportation, and communications. However, Jakarta's appeal as an economic center with high minimum wages leads to intense competition in the labor market. The Open Unemployment Rate (OUR) has fluctuated, highlighting the challenges in creating adequate employment opportunities. Additionally, Jakarta faces the demographic bonus phenomenon, with a growing productive-age population dominated by millennials and Gen Z. This demographic bonus presents opportunities for economic growth, but it requires strategies to enhance the quality of human resources to ensure optimal employment absorption and maximize the region's economic potential